ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN BETON BERTULANG MENGGUNAKAN METODE TIME STUDY - Meilani Belladona; Edito Dwi Antoro; Arif Sandra (MAJALAH TEKNIK SIMES, 2019)
Abstract Construction management work must take into account the composition of workers. recruitment of workers, direction of workers, supervision of workers and others. The composition of workers will affect work productivity. The better the qualifications of workers, the higher productivity of workers. The purpose of the study was to analyze the factors that affect worker productivity in reinforced concrete structures in the Ivory Medical Hospital construction project in the City of Bengkulu. Data collection methods use observation and data analysis using the Time Study method. Based on the calculation results obtained the value of worker productivity, namely for column formwork work; 8.92 m² / Oh, beam; 7.25 m² / Oh and plates; 24.32 m² / Oh. In column reinforcement installation work; 473.57 Kg/Oh, beam; 126.31 Kg/Oh and plates; 378.22 Kg / Oh and for column casting work; 50.44 M³/Oh, beam; 15.57 M³/Oh and plates; 5.14 M³/ Oh. The factors that cause the lack of productivity of workers in the work of installation formwork is the distance of the material sites and the number of workers, while the factors affecting reinforcement work are the weather and the position / location of the material which is very far from the installation site.